Breastfeeding: grandparents knowledge concerning Family Health Strategy - Rosineide Santana de Brito; Jullyana Davanyelle dos Santos Oliveira; Danyelle Leonette Araújo dos Santos; Amanda Barbosa da Silva (Universidade Federal de Santa Maria, 2015)
Aim: to verify knowledge ascribing grandparents in the Family Health Strategy on breastfeeding. Method: descriptive and exploratory study in a quantitative approach on 34 grandparents linked to a Family Health Unit in the city of Natal, Rio Grande do Norte, Brazil. Data were collected in August and September 2013, using structured form, treated with descriptive statistics and discussed based on the scientific literature about the theme. Results: 50% of grandparents understand that breastfeeding should be exclusive to the sixth month of the child's life, 85.9% recognize the need for the provision of this food by spontaneous demand and 38.3% know that breast milk protects against various diseases. Conclusions: the need to involve grandmothers in health promotion actions to expand their knowledge about breastfeeding to demystify beliefs about it is in evidence